Edible Coating Berbasis Kitosan dengan Penambahan Minyak Sereh dalam Memperpanjang Masa Simpan Buah Belimbing: Chitosan-Based Edible Coating with Lemongrass Oil Addition in Extending the Shelf Life of Starfruit - Sumiasih, Inanpi Hidayati; Shavira Noer Shanaz; Aziz Natawijaya (Jurnal Hortikultura Indonesia (JHI), 2022)
Starfruit belongs to the category with non-climacteric respiration patterns and is prone to perishability. Efforts to inhibit the decline in quality in both physical and chemical changes involve using edible coatings and low-temperature storage. This study aims to determine the optimal concentration of edible coating materials in maintaining the quality and shelf life of starfruit. The research was conducted from July to December 2019, at the Taman Buah Mekarsari, Bogor, West Java, and the Postharvest Laboratory of IPB. The study employed a Randomized Complete Block Design (RCBD) with two factors. The first factor was starfruit varieties consisting of two levels, Malaya and Dewi. The second factor was the edible coating consisting of five levels: without edible coating (control); chitosan 1.0% + 0.1% lemongrass oil; chitosan 1.0% + 0.2% lemongrass oil; 0.1% lemongrass oil; and 0.2% lemongrass oil. Storage was conducted at a low temperature of 15 °C. The results showed that Malaya and Dewi starfruit varieties treated with edible coating chitosan 1.0% + 0.1% lemongrass oil and control stored at 15 °C could maintain the taste and appearance of starfruit for up to 10 days after treatment. Keywords: anthocyanin, carotenoid, fruit quality, postharvest